Can a common currency foster a shared social identity across different nations? The case of the euro - Franz Buscha; Daniel Muller; Lionel Page (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2017)
Fostering the emergence of a "European identity" was one of the declared goals of the euro adoption. Now, years after the physical introduction of the common currency, we investigate whether there has been an effect on a shared European identity. We use two different datasets in order to assess the impact of the euro adoption on the fostering of a self-declared "European Identity". We find that the effect of the euro is statistically insignificant although it is precisely estimated. This result holds important implications for European policy makers. It also sheds new light on the formation of social identities.
Keywords: D02; D03; D7; H8; Z10; Z18; 330; Social Identity; European Integration; Currency Union; Difference-in-Difference